GUIDANCE IN CREATING A MASTER NUMBER BUSINESS (NIB) AND LEGAL AWARENESS BUSINESS IN MICRO, SMALL, AND MEDIUM ENTERPRISES( UMKM) KEDUNGJAYA VILLAGE USESOSS INDONESIA APPLICATION - Arin Arin; Amah Amalia; Gian Fitralisma; M. Anissul Fata; Winda Dwi Yanthi; Mohammad Bayhaki; Ade Febry Nur Fitriani; Vanessa Agatha Christy (Jurnal Abdisci, 2025)
Abstract: Background. Business Identification Number (NIB) is an essential element in business legality that provides various benefits for Micro, Small, and Medium Enterprises (MSMEs), such as access to capital, legal protection, and broader marketing opportunities. However, many MSMEs in Kedungjaya Village still do not have an NIB due to limited understanding and access to the registration process. Aims. This study aims to describe the mentoring process for making an NIB for MSMEs in Kedungjaya Village and analyze its impact on awareness of business legality. Methods. This study used a qualitative approach, using observation, interviews, and documentation techniques. Result. The study's results show that intensive assistance can improve MSME actors' understanding of the importance of business legality and accelerate the NIB registration process. In addition, increasing legal awareness among MSME actors also has a positive impact on their businesses' sustainability and development. Conclusion. Thus, assistance in making NIB can be an effective strategy in improving the legality and competitiveness of MSMEs at the local level. Implementation. This study confirms that mentoring is crucial in increasing the understanding and awareness of Micro, Small, and Medium Enterprises (MSMEs) regarding business legality. In terms of practice, this study shows that systematic and technology-based mentoring can accelerate the process of making NIB and increase MSME compliance with business regulations.